Sharing With Patients the Uncertainties Regarding the Management of Dyspepsia - Benbassat, Jochanan (Frontiers in Medicine, 2021)
Background and objective: Most clinical guidelines recommend endoscopy for dyspeptic patients at high risk of gastric cancer (above an age threshold, family history, dysphagia, loss of weight ,anemia, or childhood in Asian countries). The management of the remaining patients is uncertain. Some authors advocate endoscopy for all; others recommend various combinations between test-and-treat for Helicobacter pylori, anti-secretory treatment and/or endoscopy. The following analysis attempts to highlight the uncertainties in the choice between these strategies. Method: An overview of reported life expectancy, patient satisfaction, gastric cancer detection rates, symptom relief and cost effectiveness of the management strategies for dyspepsia. Results: Prompt endoscopy appears to be best for patient satisfaction and gastric cancer detection, and test-and-treat for H pylori - for symptom relief and avoiding endoscopies. There are no randomized controlled trials of the effect of screening by endoscopy on mortality of gastric cancer. Assuming that early diagnosis reduces this mortality as suggested by lower grades of evidence, cost effectiveness analyses indicate that mass screening in countries of high incidence gastric cancer (> 10 cases per 100,000) and targeted screening of high-risk persons in countries of low-intermediate incidence (<10 cases per 100,000) is cost-effective at a willingness to pay of $20,000 - 50,000 per QALY. Conclusions: The gain in life expectancy is the main source of uncertainty in the choice between management strategies for low-risk dyspeptic patients. I believe that, in such patients, this choice should be shared with the patients after explaining uncertainties and eliciting their preferences.